Hubungan Pengetahuan Hepatitis B dan Perilaku Berisiko Tinggi dengan Kejadian Hepatitis B pada Remaja - Satriyo Dwi Suryantoro; Pradana Zaky Romadhon; Faizal Kurniawan; Makhfudli Makhfudli; Nala Astari Pramesti; Vetty Silvana Maulida (Universitas Faletehan, 2023)
Hepatitis B is a disease caused by Hepatitis B virus (HBV) and the most common type of Hepatitis in Indonesia at 21.8%. High-risk behaviors such as unsafe sexual intercourse and indiscriminate use of syringes can cause Hepatitis B. This study aimed to analyze the relationship between knowledge of Hepatitis B and high-risk behaviors with the incidents of Hepatitis B among adolescents. The study was conducted by using a cross-sectional design and 50 adolescents as the respondents. The data collection was carried out by using a questionnaire. Correlation analysis was performed by Fisher’s exact test. 62% of adolescents had a low level of knowledge about Hepatitis B, 54% of adolescents never engaged in high-risk behavior, and 70% of adolescents claimed that they were never exposed to Hepatitis B. This study did not show any relationship between knowledge of Hepatitis B and the incidents of Hepatitis B (p 0.086 > α 0.05) and there was a relationship between high-risk behaviors in adolescents and the incidents of Hepatitis B (p 0.002 < α 0.05). Adolescents' knowledge of Hepatitis B and high-risk behaviors in adolescents are important factors that need to be controlled to decrease Hepatitis B rates. Socialization of Hepatitis B knowledge is needed to understand the virus, causes, transmission channel, how to stop the spread, and treatments should be taken when being infected by Hepatitis B virus.